Coinfection by Hepatitis C Is Strongly Associated with Abnormal CD4/CD8 Ratio in HIV Patients under Stable ART in Salvador, Brazil - Clara Brites-Alves; Eduardo Martins Netto; Carlos Brites (Journal of Immunology Research)
Proper immune restoration (CD4 count >500 and normal CD4/8 ratio) is reached only by a fraction of HIV patients, despite stable viral suppression. Methods. We present a case-control study to compare HIV patients with viral suppression >1 year, according to immune restoration pattern: adequate response (AR) defined by CD4 > 500 cells/mm3 and CD4/8 ratio >1; partial response (PR = patients with CD4 > 500, but CD4/8 ratio <1); inadequate response (IR = CD4 < 500 cells). Results. We evaluated 293 consecutive patients (89 AR, 112 PR, and 92 IR), 70% males. Male gender (p<0.01), lower mean CD4 nadir (p<0.001), higher baseline VL (p=0.01), previous diagnosis of Tb (p=0.03), or HCV (p<0.01) was associated with IR. Likelihood of AR/PR was similar regardless of gender, after adjusting for nadir CD4+ cells count. Longer time under suppressive ART was also associated with a greater chance of AR, but logistic regression identified coinfection by HCV as the main factor associated with abnormal CD4/CD8 ratio. Conclusion. Early initiation of ART and longer time since first undetectable PVL were predictors of AR. Previous HCV diagnosis significantly increases the risk of abnormal CD4/CD8 ratio.